2016
DOI: 10.1523/jneurosci.2002-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacologic Manipulation of TLR4 Has Minimal Impact on Ethanol Consumption in Rodents

Abstract: Toll-like receptor 4 (TLR4) is a critical component of innate immune signaling and has been implicated in alcohol responses in preclinicaland clinical models. Members of the Integrative Neuroscience Initiative on Alcoholism (INIA-Neuroimmune) consortium tested the hypothesis that TLR4 mediates excessive ethanol drinking using the following models: (1) Tlr4 knock-out (KO) rats, (2) selective knockdown of Tlr4 mRNA in mouse nucleus accumbens (NAc), and (3) injection of the TLR4 antagonist (ϩ)-naloxone in mice. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 76 publications
4
57
2
2
Order By: Relevance
“…Despite these findings suggesting a prominent role of TLR4 in alcohol-induced behaviors, a recent report provides evidence that TLR4 is not involved in alcohol consumption. In this report, both pharmacological and genetic manipulations of TLR4 fail to significantly alter excessive alcohol consumption utilizing a two-bottle choice paradigm, drinking-in-the-dark procedure and a chronic intermittent exposure procedure (Harris et al, 2016). These findings suggest that the alcohol-induced immune activation of microglia contribute to alcohol drinking and the subjective effects of alcohol administration, although the role of TLR4 remains unclear.…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 96%
“…Despite these findings suggesting a prominent role of TLR4 in alcohol-induced behaviors, a recent report provides evidence that TLR4 is not involved in alcohol consumption. In this report, both pharmacological and genetic manipulations of TLR4 fail to significantly alter excessive alcohol consumption utilizing a two-bottle choice paradigm, drinking-in-the-dark procedure and a chronic intermittent exposure procedure (Harris et al, 2016). These findings suggest that the alcohol-induced immune activation of microglia contribute to alcohol drinking and the subjective effects of alcohol administration, although the role of TLR4 remains unclear.…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 96%
“…Indeed, alcohol self‐administration increases expression of the TLR4 protein in the VTA of alcohol‐preferring rats (June et al ., ). Mice lacking the TLR4 protein or the TLR4 adaptor protein, MyD88, display lower sensitivity to the sedative and motor‐impairing effects of alcohol compared to wild‐type mice (Wu et al ., ; Harris et al ., ), whereas MYD88 knockout increases ethanol consumption (Blednov et al ., ). TLR4 activation in the VTA and central amygdala, in particular, may be an important signal for binge alcohol consumption, as site‐selective knockdown of TLR4 in these regions using siRNA reduces binge drinking in alcohol‐preferring rats (Liu et al ., ; June et al ., ).…”
Section: Glial Mechanisms Underlying Behavioral Changes After Drug Exmentioning
confidence: 99%
“…Furthermore, genetic knockout of TLR2 or CD14, suppresses ethanol intake . In contrast, some have reported no effect of pharmacological or genetic manipulation of TLR4 on excessive alcohol consumption in the two-bottle choice, drinking-in-the-dark, or chronic intermittent access paradigms Harris et al, 2017). Blednov et al (2017) demonstrated that TLR4 mutant mice have unaltered alcohol consumption behavior.…”
Section: Manipulations Of Tlr4 Function Modulate Drug-associated Behamentioning
confidence: 99%
“…Although it still remains unclear whether immune receptors, TLRs, are involved in alcohol drinking in adult animals (Harris et al, ), recent studies have shown that blocking the TLR4 response using selective inhibitor 5342126 decreases ethanol drinking in both ethanol‐dependent and nondependent mice (Bajo et al, ). Adult TLR4‐deficient adolescent female mice exposed to alcohol in adolescence appear to be protected against escalation in alcohol preference (Montesinos, Pascual, et al, ).…”
Section: Impact Of Immune System Activation On Alcohol‐induced Brain mentioning
confidence: 99%